AN ANALYTICAL STUDY OF MANIPUR PAINTINGS IN PRE AND POST INDIA INDEPENDENCE - Meinam, Irikhomba Meetei (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Painting is considered as one of the oldest art forms. Every civilization has its own history of painting. Painting deals with the pigment which is used to apply on the surface by using a binder. During the early period, man used to communicate through pictographic forms by depicting drawings and paintings on the wall surfaces. From the course of time drawing and painting have been a major part of transforming our human civilization. Manipur was one of the princely kingdoms in the earlier time. The people of this state were very talented and skillful. They used to practice art activities based on their livelihood and the official purposes of the royal court. Visual art has taken a very important role in the formation of Manipur tradition and culture. After the Vaishnavite religion introduced in Manipur, two types of painting styles were visible in the state before the India got independence. Formal art education was started lately after the British introduce in Manipur. The trend and development of Visual Art activities in the state were closely associated with the art development in the mainland states. The paper attempt to analyzed and narrate the art practice that happen in two decades of Manipur history i.e., Art trend before India Independent and post Indian Independent.